Rett syndrome: A study of the face - Allanson, Judith E.; Hennekam, Raoul C.M.; Moog, Ute; Smeets, Eric E. (American journal of medical genetics, 2011)
Rett syndrome is a unique disorder of neurodevelopment that is characterized by an evolving behavioral and developmental phenotype, which emerges after an apparently normal early infantile period. It almost exclusively affects females. The face of Rett syndrome is said to resemble that of Angelman syndrome, although there seems little objective support for this impression and it is not a concept with universal support. This observational and anthropometric study was carried out to define the key facial characteristics of females with Rett syndrome and to evaluate whether any changes of significance occur with age. Thirty-seven affected Caucasian females, from 2 to 20 years of age, were evaluated. Thirty-five of them had a documented mutation in MECP2 while the remaining two fulfilled the clinical criteria for Rett syndrome and had been diagnosed by an experienced clinician. Few unusual facial features were noted. Almost all facial measurements were within the normal range although head circumference tended to fall below the normal range with increasing age. The pattern of measurements was constant over time, with the exception of increased facial width in the under 3-year-old girls. The face of Rett syndrome does not demonstrate marked prognathism, wide mouth, spaced teeth or striking microcephaly, all features of Angelman syndrome. Thus, while Rett and Angelman syndromes have similar clinical, neurological, and behavioral phenotypes, they do not appear to share similar facial features. © 2011 Wiley-Liss, Inc.